If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -6x = -4(4 + -2x) 9 + -6x = (4 * -4 + -2x * -4) 9 + -6x = (-16 + 8x) Solving 9 + -6x = -16 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + -6x + -8x = -16 + 8x + -8x Combine like terms: -6x + -8x = -14x 9 + -14x = -16 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -14x = -16 + 0 9 + -14x = -16 Add '-9' to each side of the equation. 9 + -9 + -14x = -16 + -9 Combine like terms: 9 + -9 = 0 0 + -14x = -16 + -9 -14x = -16 + -9 Combine like terms: -16 + -9 = -25 -14x = -25 Divide each side by '-14'. x = 1.785714286 Simplifying x = 1.785714286
| 0.55[f-32]=25 | | (7x+5)=0 | | 24x^4+16x^2-8=0 | | sqrt64/25 | | 4x=3(2+1x) | | 30+25x=105 | | x^2-12x+48=4 | | -3x+14=x-10 | | 12x+3y-(4x-2y)= | | M=10+-1m | | Cos(6x)+cos(4x)=o | | (1-3x)=0 | | 2x+5x=10x+60 | | 2A+10X^4C=0 | | 12x-3y-2(4x+y)= | | 2x-20=80 | | 7x+8y+3(2x+4y)= | | 5a+7a-6b-3a= | | 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q |